Implementasi Guided Discovery Learning dalam Kurikulum Spiral Pelajaran Grammar dan Dampaknya Terhadap Penguasaan Konsep, Keterampilan Menulis dan Motivasi Belajar - Cicilia Ika Mayawati; Clara Evi C. Citraningtyas (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This study examines the implementation of the Guided Discovery Learning method in Grammar lessons at the end of the implementation of the spiral curriculum with the aim of knowing that there are differences in mastery of concepts, writing skills and learning motivation between the Grade VI students who take part in the Guided Discovery Learning method and the students who take part in learning using the Guided Discovery Learning method. The research was conducted for 10 weeks at Charis Global School Lippo Cikarang. There were 36 students who took part in this research, 18 students from Steve Jobs class as the control group and 18 students from Elon Musk class as the experimental group. This research is a quasi-experimental research involving the experimental group and the control group. The research instruments used to collect the data were test questions, observation sheets and rubrics that had been tested for validity and reliability. The mean and n-gain values ​​obtained were then tested to find the differences between the two classes through the t- test. Based on the results of the data analysis, it can be concluded that the implementation of the Guided Discovery Learning method has a significant impact on the students’ concept mastery, writing skills and learning motivations.